Historiographical Disputes on Serbs’ Migration in the Early Modern Period. A Side-Commentary to the Rajko Veselinović and Gligor Stanojević Polemic (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
Disputes between historians have always been a significant part of historiographical research. On the one hand, they allow to reconsider the existing state of knowledge; on the other, they set new research directions. The main objective of this article is to present the polemic between two Serb historians – Rajko Veselinović and Gligor Stanojević – which was ongoing in the periodical publications between 1978 and 1984. The assessment of particular persons and events related to the migration of Serbs in the early modern period was the main focus of their study, as well as the matter in dispute between the researchers. Thus, in the article, difficulties with the geographical and ethnical nomenclature within the Balkan Peninsula had been discussed. What was revised were the researchers’ opinions on the role that the Serbian Orthodox Church and particular historic persons played in the migration of Serbs from Kosovo and the Metohija territories to the lands on the north of Sava and Danube rivers on the turn of the 17th and 18th century. The article also features a couple of observations on the social-demographical development on the lands where the Serbs lived.